The tie-up blues for Vanya's Dance Planet: A failure case of social media marketing1. Issue 2 (4th October 2022) - Kushwaha, Pooja S
This case study covers various aspects of social media as an alternative and cost-effective tool of marketing and promotion. The case also highlights the social media promotion tools used by a social media consultancy start-up for a client, and how it failed to achieve desired results. In this world of digitisation, social media marketing is a trend that is prevalent across the globe. Social networks have changed the way information is delivered to the customers, shifting from traditional push marketing to pull marketing. Entrepreneurs are using social media marketing to promote their product or services by this they can not only promote their venture but at the same time efficiently utilise their marketing budget. Vanya's Dance Planet is such an organisation which used social media marketing to reach out to its target prospective customers. It required structured planning, professional knowledge about various social media platforms, and creative writing skills to post content on these platforms. The consultant organisation We4U planned and executed the social media campaigns for Vanya's Dance Planet getting professional help from social media consultancy start-ups which can be a wise decision for some entrepreneurial ventures. But sometimes these professional tie-ups would end up with loss of time, money and trust. This case study deliberates upon such a fallout.